Retrospective Analysis of High-Dose Intrathecal Morphine for Analgesia after Pelvic Surgery. (2011) - Rebel, Annette; Sloan, Paul; Andrykowski, Michael
Abstract : BACKGROUND: The effectiveness of intrathecal opioids (ITOs) for postoperative analgesia has been limited by reduced opioid dosing because of opioid-related side effects, most importantly respiratory depression. To overcome these limitations, high-dose intrathecal morphine was combined with a continuous intravenous (IV) postoperative naloxone infusion. The aim of the present chart analysis was to investigate the safety and efficacy of high-dose ITOs combined with IV naloxone compared with IV opioid analgesia alone. METHODS: A retrospective chart analysis was performed on 121 female patients requiring major pelvic surgery. Ninety-eight patients received a single injection of high-dose ITOs before administration of typical general anesthesia, followed by an IV naloxone infusion at 5 μg/kg/h started post-ITO and continued for 22 h postoperatively. Twenty-three patients were given IV morphine (IVM) for postoperative analgesia and served as a reference group. Postoperative pain relief, analgesic consumption and ability to ambulate were assessed for 48 h postoperatively. Treatment safety was assessed by monitoring opioid-related side effects and vital signs. Data are presented as mean ± SD. RESULTS: Mean ITOs given were morphine 1.1±0.2 mg combined with fentanyl 49±6 μg. The mean worst pain visual analogue scale score in the first 12 h postoperatively was 0.2±0.90 in the ITO group versus 4.3±3.0 in the IVM group (P<0.05). On postoperative day 2, the mean worst pain visual analogue scale score was only 1±1.8 in the ITO group versus 4.1±2.6 in the IVM group (P<0.05). Analgesic requirements were reduced in the ITO group. In the first 24 h, the ITO group used 6.8±10.2 morphine equivalents (mg IV) versus 76.1±44.4 in the IVM group (P<0.05). All patients in the ITO group were able to ambulate in the first 12 h postoperatively compared with 17/23 in the IVM group. There was a higher incidence of opioid-related sedation in the IVM group. Other opioid-related side effects were infrequent and minor in both groups. CONCLUSIONS: High-dose ITOs combined with a postoperative IV naloxone infusion provided excellent analgesia for major pelvic surgery. The IV naloxone infusion combined with high-dose ITOs appeared to control opioid side effects without affecting analgesia.